Research Skills in Postgraduate Education. A Qualitative Analysis - Zambrano Sandoval, Heidy Johanna; Chacón Corzo, Carmen Teresa (Revista Educación - Journal of Education, 2021)
This study analyzes the Venezuelan Seminary I and Seminary II program syllabi in terms of teaching research skills to graduate-level students based on qualitative analysis of the Master's programs syllabus in Educational Administration, Industrial Maintenance and Teaching of Basic Sciences offered Venezuelan university. Criteria included internal coherence and didactic sequence or continuity. According to the findings, these programs focus attention on the completion of the various stages of graduate work (thematic, proposal, research progress and final defense) required for completing a Master's degree, as a series of steps ignoring the process of integration and continuity in order to develop the result. It is concluded that there’s a need to improve and update the syllabi in light of the skills-based approach to develop research sills and contribute to postgraduate researcher training.